2010
DOI: 10.1111/j.1748-5827.2009.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Coombs’, haemoplasma and retrovirus testing in feline anaemia

Abstract: Coombs', haemoplasma and retrovirus testing in feline anaemia INTRODUCTIONAnaemia is commonly encountered in feline practice and arises due to many different causes (Weingart and others 2004). One cause of anaemia is haemolysis following the binding of antibody and/or complement molecules to the surface of erythrocytes (Switzer and Jain 1981). In cats, such immune-mediated haemolytic anaemia (IMHA) is often secondary to an underlying cause such as haemoplasma infection, feline leukaemia virus (FeLV) infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 50 publications
4
36
2
Order By: Relevance
“…Traditionally, there also were concerns that the DAT had an unacceptably low specificity for diagnosis of IMHA because clinically relevant titers were obtained from nonanemic cats in a previous study . A more recent study using a more complete panel of monovalent antisera directed against IgM and IgG isotypes indicated that a clinically relevant positive titer with either monovalent or polyvalent antisera at 37C had a sensitivity of 81% and specificity of 92% for diagnosis of IMHA, suggesting that this DAT should be considered as a diagnostic test more frequently, particularly in those cases without convincing autoagglutination or ghost cells. The relatively low sensitivity of the DAT may create difficulties if used as a sole diagnostic test because cases of presumed primary IMHA have been reported in the absence of a clinically relevant titer, both in a previous study and in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, there also were concerns that the DAT had an unacceptably low specificity for diagnosis of IMHA because clinically relevant titers were obtained from nonanemic cats in a previous study . A more recent study using a more complete panel of monovalent antisera directed against IgM and IgG isotypes indicated that a clinically relevant positive titer with either monovalent or polyvalent antisera at 37C had a sensitivity of 81% and specificity of 92% for diagnosis of IMHA, suggesting that this DAT should be considered as a diagnostic test more frequently, particularly in those cases without convincing autoagglutination or ghost cells. The relatively low sensitivity of the DAT may create difficulties if used as a sole diagnostic test because cases of presumed primary IMHA have been reported in the absence of a clinically relevant titer, both in a previous study and in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…9 White blood cell (WBC) count, WBC differential counts, platelet count and any abnormalities [polychromasia, anisocytosis, acanthocytes, agglutination, elliptocytes, hypochromasia, Heinz bodies (HB) numbers and percentages, nucleated RBCs, macrocytosis, microcytosis, schistocytes and toxic neutrophils], detected on a Wright's stained blood smear, were recorded as absent, slight, mild, moderate or severe. 9 Test results for feline immunodeficiency virus (FIV), feline leukaemia virus (FeLV), haemoplasma (three species) infection and other clinicopathological data [prothrombin time (PT), 10 activated partial thromboplastin time (aPTT), 10 Coombs' test, 11 bone marrow (BM) aspirate and core biopsy results and post-mortem findings] were recorded when performed.…”
Section: Data Recordingmentioning
confidence: 99%
“…Cold agglutinins in healthy cats were identified in early studies of feline blood groups and in an earlier study, where 9 of 20 healthy client‐owned cats (45%) had positive results (1:2 dilution) at 4°C. However, in studies of experimental hemoplasma infection and naturally occurring cases of anemia, no healthy cats have had positive results at 4°C . Agglutination in the control well of a DAT indicates antibody‐induced persistent agglutination, and is most commonly associated in cats with immune‐mediated hemolytic anemia .…”
Section: Antinuclear Antibody and Direct Antiglobulin Test Results Inmentioning
confidence: 99%